Social–Emotional and Educational Needs of Higher Education Students with High Abilities: A Systematic Review - Marianne Nannings; Marjolijn van Weerdenburg; Petrie J. A. C. van der Zanden; Lianne Hoogeveen (Behavioral Sciences)
Students with high intellectual abilities in higher education face a significant risk of underachievement due to a range of influencing factors. This systematic review explored their social–emotional and educational needs and examined interventions aimed at addressing both these needs and underachievement. A systematic literature search of a total of 118 records identified 20 social–emotional and 26 educational needs, organized into six overarching categories, illustrating the complex challenges these students face. Of the 42 records investigating an intervention, 38 focused on students directly, three on student advisors and one on teachers. While most interventions addressed multiple student needs, none fully integrated social–emotional and educational aspects. Ultimately, 17 studies examined underachievement, but only 5 implemented an intervention to reduce it. These findings underscore the need for integrated approaches to effectively support higher education students with high abilities.